The World in Conflict : understanding the world's troublespots - Andrews, John (London: The Economist, 2022)
"The world today rests on increasingly unstable fault lines. From the conflict in Ukraine or fresh upheavals in the Middle East to the threats posed to humanity by a global pandemic, climate change, and natural disasters, the world's danger zones once again draw their battle lines across our hyper-connected, yet fragmented globe. In this revised and updated fourth edition, join veteran Economist journalist John Andrews as he analyzes the old enmities and looming collisions that underlie conflict in the twenty-first century."--Jacket flap.
Why conflict happens -- Middle East and north Africa : connected by Islam -- Africa : rich in resources, poor in governance -- The UK and Europe : bloodied past, complacent present, uncertain future -- The Americas : faith, drugs and revolution -- The United States : both superpower and vulnerable Goliath -- Asia : people and potential--for both peace and war -- War without end? -- Appendix: Terrorist organizations : to designate and to proscribe.
Keywords: International Relations; World Politics -- 21st century; Conflict Management; Relations International